Hypophosphataemia after major hepatectomy and the risk of post‐operative hepatic insufficiency and mortality: an analysis of 719 patients. Issue 10 (15th May 2014) - Squires, Malcolm H.; Dann, Gregory C.; Lad, Neha L.; Fisher, Sarah B.; Martin, Benjamin M.; Kooby, David A.; Sarmiento, Juan M.; Russell, Maria C.; Cardona, Kenneth; Staley, Charles A.; Maithel, Shishir K.
Abstract Background Hypophosphataemia after a hepatectomy suggests hepatic regeneration. It was hypothesized that the absence of hypophosphataemia is associated with post‐operative hepatic insufficiency (PHI) and complications. Methods Patients who underwent a major hepatectomy from 2000–2012 at a single institution were identified. Post‐operative serum phosphorus levels were assessed. Primary outcomes were PHI (peak bilirubin >7 mg/dl), major complications, and 30‐ and 90‐day mortality. Results Seven hundred and nineteen out of 749 patients had post‐operative phosphorus levels available. PHI and major complications occurred in 63 (8.8%) and 169 (23.5%) patients, respectively. Thirty‐ and 90‐day mortality were 4.0% and 5.4%, respectively. The median phosphorus level on post‐operative‐day (POD) 2 was 2.2 mg/dl; 231 patients (32.1%) had phosphorus >2.4 on POD2. Patients with POD2 phosphorus >2.4 had a significantly higher incidence of PHI, major complications and mortality. On multivariate analysis, POD2 phosphorus >2.4 remained a significant risk factor for PHI [(hazard ratio HR):1.78; 95% confidence interval (CI):1.02–3.17; P = 0.048], major complications (HR:1.57; 95%CI:1.02–2.47; P = 0.049), 30‐day mortality (HR:2.70; 95%CI:1.08–6.76; P = 0.034) and 90‐day mortality (HR:2.51; 95%CI:1.03–6.15; P = 0.044). Similarly, patients whose phosphorus level reached nadir after POD3 had higher PHI, major complications and mortality. Conclusion Elevated POD2 phosphorus levels >2.4 mg/dl and a delayed nadir in phosphorus beyond POD3 are associated with increased post‐operative hepatic insufficiency, major complications and early mortality. Failure to develop hypophosphataemia within 72 h after a major hepatectomy may reflect insufficient liver remnant regeneration.